PENGARUH GAYA KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI DI DINAS BALAI BAHASA PROVINSI BALI - Yudi Prawira Jaya, Kadek; Dewi Adnyani, I Gst. Ayu (E-Jurnal Manajemen; Vol 4 No 9 (2015), 2015)
The purpose of this study was to determine the effect of transformational leadership style, transactional leadership style and autocratic leadership style on employee discipline in the Department of Language Center Bali Province. The methods of collection data is questionnaires, with a total population of 58 people. Sampling method is a method of census, with a total sample of 58 respondents. Data were analyzed using multiple linear regression analysis. The results showed transformational leadership style, transactional leadership style and autocratic leadership style and a significant positive effect on the discipline of work in the Department of Language Center Bali Province.
Keywords: Transformational Leadership Style, Transactional Leadership Style, Autocratic Leadership Style, Employee Discipline